Open channel hydraulics - Akan, A. Osman. (Elsevier/BH, 2006)
Open Channel Hydraulics is written for undergraduate and graduate civil engineering students, and practicing engineers. Written in clear and simple language, it introduces and explains all the main topics required for courses on open channel flows, using numerous worked examples to illustrate the key points. With coverage of both introduction to flows, practical guidance to the design of open channels, and more advanced topics such as bridge hydraulics and the problem of scour, Professor Akan's book offers an unparalleled user-friendly study of this important subject Clear and simple style suited for undergraduates and graduates alike Many solved problems and worked examples Practical and accessible guide to key aspects of open channel flow.